Dendritic fibrous NiMn2O4 in concrete-based materials for oxidative desulfurization of real fuel - Seyed Mahdi Saadatmand; Amin Honarbakhsh; Seyed Mojtaba Movahedifar; Mehdi Nobahari; Rahele Zhiani (Results in Chemistry)
Dendritic nanofibrous NiMn2O4 (DFNiMn2O4) was sustainably synthesized from Ni(NO3)2 and Mn(NO3)2. It was subsequently incorporated into concrete mortar. The effectiveness of DFNiMn2O4 and photocatalytic mortar in light-driven petroleum desulfurization was evaluated. The photoluminescence spectra and desulfurization efficiency of the DFNiMn2O4, after immersion in an artificial concrete pore fluid, were assessed to determine its synthetic steadfastness. The desulfurization efficiency of the mortar enhanced as the DFNiMn2O4 dosage increased. This concrete demonstrates excellent efficiency in promoting desulfurization under environmentally sustainable conditions. The approach outlined in this study provides multiple advantages, such as considerable economic benefits and compatibility with diverse functional groups. Additionally, these reactions can efficiently process various compounds, including synthetic fuels, sulfur mustard simulants, and natural gasoline. The study revealed that the addition of DFNiMn2O4 improved the durability, mechanical properties, and overall resilience of the cement samples. The incorporation of DFNiMn2O4 led to a decrease in chloride ion permeability and a reduction in the material's void volume. Additionally, the presence of DFNiMn2O4 enhanced the cement mortar's ability to resist compressive forces compared to the control samples.